Aplikasi Pupuk Kandang Kambing dan ZPT Atonik pada Tanaman Melon Varietas Sky Rocket (Cucumis Mello L) - Muhammad Habib; Novilda Elizabeth Mustamu; Khairul Rizal (JURNAL MAHASISWA AGROTEKNOLOGI (JMATEK), 2020)
This research was carried out in the agricultural field of the University of Harbor. The research began from March to June sky research (Cucumis Mello L) to determine the effect of giving fertilizers and goats and cultivating land on the growth and production of melon sky rocket varieties (Cucumis Mello L). This study used a Factorial Randomized Block Design (RCBD) with 2 factors examined and repeated 3 times. Goat MANURE (K) fertilizer dosing factor consists of 3 levels, namely: K0 = No treatment, K1 = 1 kg / Plot and K2 = 2 kg / Plot. The inhalation factor (G) consists of 3 levels, namely G0 = Tanpaper treatment, G1 = 1cc / L water / plot and G2 = 2cc / L water / plot. The administration of goat manure significantly affects the observation of plant height, number of branches, fruit weight, number of plots and the weight of plots. The application of ZPT has a significant effect on the observation of plant height and number of branches but has no significant effect on observing the weight of fruit per plots, the number of plots and the weight of per seed. The interaction between goat manure and ZPT did not significantly affect all observations. Keywords:Goat Manure, ZPT, Melond